Government veterinarians' perceptions of routine biosecurity focused on dairy cattle farms in north-western and north-eastern Spain - Moya, Sebastián; Navea, José; Casal, Jordi; Ciaravino, Giovanna; Yus, Eduardo; Diéguez, Francisco Javier; Benavides, Bibiana; Tirado, Francisco; Allepuz, Alberto (Frontiers in Veterinary Science, 2023)
The implementation of biosecurity measures in livestock production systems can be affected by the psychosocial factors of its stakeholders, which can be observed through their knowledge, attitudes and perceptions/practices. In Spain, there are no regulations per se to promote biosecurity. Of all stakeholders, farmers and veterinarians have been addressed in previous biosecurity studies, but not veterinarians belonging specifically to the government services. This study explores this particular group’s perceptions of routine biosecurity in livestock production systems in north-western and north-eastern Spain, an understanding of which could help to improve the implementation of biosecurity measures on farms. Eleven interviews were conducted with veterinarians from different levels of the government services in Galicia and Catalonia, and were analysed through content analysis. Dairy cattle farms were considered as the reference livestock production systems. The respondents stress the limited availability of staff and time resources for biosecurity. The advisory role of government veterinarians is not well recognised among farmers, who feel that their services prioritise their sanctioning role. In fact, government veterinarians consider that farmers only implement biosecurity measures to avoid being sanctioned, and not because they are aware of the importance of biosecurity. Meanwhile, the participants comment that biosecurity regulations should be flexible and need to consider the contexts of the farms where biosecurity measures are implemented. Finally, government veterinarians are willing to attend biosecurity meetings together with all farm stakeholders, at which the government services could be informed about biosecurity issues on farms. The person who could take on the biosecurity advisory role should be defined, along with further discussion of such matters as the responsibilities of each stakeholder. Government veterinary services need to be considered in studies of biosecurity operations in order to improve their implementation. It is therefore concluded that government veterinarians are seeking to balance their own institutional perspective with that of farmers and veterinarians in the routine implementation of biosecurity measures.